Kajian Etnobotani Tanaman Aromatik di Desa Air Putih Kecamatan Pinang Berlapis Lebong Bengkulu - Juwita EN Purba; RR Sri Astuti; Fatimatuzzahra -; Dedi Satriawan; Evelyne Riandini (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Aromatic plants are plants that can produce essential oils, contain volatile substances and have a distinctive aroma. The ethnobotanical study of aromatic plants aims to find out the types of aromatic plants used by the community and how to apply. This research was carried out in April-June 2024 at Air Putih Village and Botanical Laboratory, Basic Science Building, FMIPA UNIB. The method of open interviews with informants was carried out to find out the use of aromatic plants. The results of the study obtained 10 species of aromatic plants belonging to 5 families, namely Alpinia galanga (L.) Willd., Amomum compactum Sol. ex Maton, Curcuma domestica Val., Curcuma zanthorrhiza Roxb., Zingiber cassumunar Roxb., Zingiber officinale var rubrum included in the family Zingiberaceae, Cymbopogon citratus (DC.) Stapf (Poaceae), Acorus calamus L. (Acoraceae), Pandanus amaryllifolius Roxb. ex Lindl (Pandanaceae), and Myristica fragrans Houtt. (Myristicaceae). The most used plant organs are rhizomes 60%, followed by leaf organs 50%, and fruits 20%. The community processes aromatic plants by boiling 70%, cooking spices 60%, diced 30%, grated 20%, crushed and boiled 20%, covered 10%, sliced 10%, and tied 10%.